Trump Is Not a (Condorcet) Loser! Primary Voters' Preferences and the 2016 Republican Presidential Nomination. Issue 3 (July 2020) - Woon, Jonathan; Craig, Sean; Leifson, Amanda; Tarpey, Matthew
ABSTRACT: Many commentators argued that if elites and voters had coordinated on an alternative candidate, Donald Trump could have been defeated for the 2016 Republican presidential nomination. This claim rests on the implicit assumption that Trump would have been defeated in a head-to-head contest against another candidate—that he was a Condorcet loser. Conventional pre-election polls, however, do not provide enough information about voters' preferences to assess the plausibility of this claim. Relying on novel data to construct individuals' complete preferences over the set of leading Republican candidates, we find that no other candidate strictly defeats Trump in pairwise majority-rule comparisons and—far from being a Condorcet loser—that Trump is a member of the majority-rule core. Our results question the plausibility of the coordination narrative because Trump's support was wider than political observers believed: it came from a broad base of the Republican primary electorate rather than a small but intense minority.